Neuronal entropy depends of the level of alertness: data - Andres, Daniela Sabrina (2023)
Microelectrode recordings (MER) obtained from adult rats weighing 250–350 g. assigned to the control group of an experimental Parkinson’s research protocol (Andres et al., 2014). The goal of the experiments was to record the spontaneous activity of the globus pallidus pars interna (GPi, previously called entopeduncular nucleus) under conditions of alertness, environmental silence and blindfoldednes.